2018
DOI: 10.1007/s10884-018-9646-2
|View full text |Cite
|
Sign up to set email alerts
|

Invariance Pressure for Control Systems

Abstract: Notions of invariance pressure for control systems are introduced based on weights for the control values. The equivalence is shown between inner invariance pressure based on spanning sets of controls and on invariant open covers, respectively. Furthermore, a number of properties of invariance pressure are derived and it is computed for a class of linear systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Invariance pressure. In this subsection we recall the concepts of invariance and outer invariance pressure introduced in Colonius, Cossich and Santana [6,7] and some of their properties.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Invariance pressure. In this subsection we recall the concepts of invariance and outer invariance pressure introduced in Colonius, Cossich and Santana [6,7] and some of their properties.…”
Section: Preliminariesmentioning
confidence: 99%
“…For the inner invariance pressure of discrete time systems, one considers sets which are (τ, K, intQ)-spanning. Here again finite spanning sets are sufficient (the proof given in [6,Propositon 5] for the case K = Q easily extends to admissible pairs (K, Q)).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Invariance pressure, as a generalization of invariance entropy, was first introduced by Colonius, Santana, and Cossich [8,4]. Recently, the same authors in [7] obtain some bounds of invariance pressure and get an explicit formula for hyperbolic linear control systems.…”
Section: (Communicated By Xiangdong Ye)mentioning
confidence: 99%
“…Measure-theoretic versions of invariance entropy have been considered in Colonius [4] and Wang, Huang, and Sun [15]. Invariance pressure has been analyzed in Colonius, Cossich, and Santana [1,2,3]. In Zhong and Huang [18] it is shown that several generalized notions of invariance pressure fit into the dimension-theoretic framework due to Pesin.…”
Section: Introductionmentioning
confidence: 99%